STRATEGI PENGEMBANGAN HUTAN MANGROVE DI KECAMATAN JORONG KABUPATEN TANAH LAUT KABUPATEN KALIMANTAN SELATAN - Aldha Alfian Noer Dwi; Abdi Fithria; Kissinger Kissinger (Jurnal Hutan Tropis, 2021)
Mangrove forests in South Kalimantan have been converted into fish ponds, settlements, ports and other uses. The condition of damaged mangrove forests is very alarming. The purpose of this study is to formulate a development and conservation strategy for mangrove forests in Jorong District. This research uses interviews, direct observation in the field to analyze the factors that cause mangrove damage, descriptive analysis through the In depth interview approach with key information about to formulate a strategy for developing and conserving mangrove forests in Jorong District. The results of changes in the distribution and extent of mangroves decreased from 2010 (2.324 ha) to 2020 (1.665 ha). The dynamics of mangrove damage are caused by mining activities and oil palm company expansion. The formulation of the strategy is socialization to the community related to the development of mangrove forests that contribute to high biota, the concept of developing mangrove ecotourism to improve the living standards of the poor, applying the pattern of developing mangrove forests for the common good.